DEVELOPMENT OF INTERACTIVE MULTIMEDIA BASED ON ARTICULATE STORYLINE ON ETHNIC AND CULTURAL DIVERSITY MATERIAL IN INDONESIA CLASS IV SDN 1 LENGKONG NGANJUK DISTRICT - Caroline Sugiarto; Wahyudi Wahyudi; Sutrisno Sahari (Universitas Labuhanbatu, 2023)
The background of this research is the observation of class IV teachers at SDN 1 Lengkong, Nganjuk Regency. In the teaching and learning process, the teacher does not use learning media and is only fixated on textbooks as the only source of teaching and learning so that students tend to have difficulty understanding the material taught by the class teacher. The formulation of the research problem: How is the validity, practicality, effectiveness of articulate storyline-based interactive multimedia for material on ethnic and cultural diversity in Indonesia in class IV students at SDN 1 Lengkong? In this study using the type of research and development (Research and Development). The model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) developed by Sugiyono. The research subjects were fourth grade students at SDN 1 Lengkong. The results of the study (1) The results of the validation of media experts obtained a percentage of 84.5% and material experts 95%. The average level of validity score is 90%, it can be stated that it is very valid. (2) The results of the student response questionnaire obtained a percentage of 94% and the teacher's response questionnaire was 86%. The average level of practicality gets a score of 90%, it can be stated that it is very practical. (3) The results of limited trials obtained a percentage of 84% and 87% of wide trials. The average level of effectiveness gets a score of 85.5%, so it can be stated that it is very significant.Keywords: interactive multimedia, articulate storyline, ethnic and cultural diversity Abstrak Latar belakang penelitian ini ialah observasi guru kelas IV SDN 1 Lengkong Kabupaten Nganjuk. Dalam proses belajar mengajar, guru tidak menggunakan media pembelajaran dan hanya terpaku pada buku teks sebagai satu-satunya sumber belajar mengajar sehingga siswa cenderung sulit memahami materi yang diajarkan oleh guru kelas. Rumusan masalah penelitian ini: Bagaimana kevalidan, kepraktisan, keefektifan multimedia interaktif berbasis articulate storyline untuk materi keberagaman suku dan budaya di Indonesia pada siswa kelas IV SDN 1 Lengkong? Pada penelitian ini menggunakan jenis penelitian dan pengembangan (Research and Development). Model yang digunakan adalah model ADDIE (Analysis, Design, Development, Implementation, Evaluation) yang dikembangkan oleh Sugiyono. Subjek peneliian ialah siswa kelas IV SDN 1 Lengkong. Hasil dari penelitian (1) Hasil validasi ahli media diperoleh presentase 84,5% dan ahli materi 95%. Rata-rata tingkat kevalidan skor 90%, dapat dinyatakan sangat valid. (2) Hasil angket respon siswa diperoleh presentase 94% dan angket respon guru 86%. Rata-rata tingkat kepraktisan mendapatkan skor 90%, dapat dinyatakan sangat praktis. (3) Hasil uji coba terbatas diperoleh presentase 84% dan uji coba luas 87%. Rata-rata tingkat keefektifan mendapatkan skor sebesar 85,5%, sehingga dapat dinyatakan bahwa sangat signifikan.Kata Kunci: multimedia interaktif, articulate storyline, keberagaman suku dan budaya